PENGETAHUAN REMAJA USIA 16 â 18 TAHUN TENTANG SENAM OTAK - Suryono, Suryono (Akademi Keperawatan Pamenang, 2014)
Gymnastics of brain is connecting an exercise line up of the simple body movement that movement is made for stimulating left-brain and right-brain; lighting or relaxing back brain and part of front-brain; stimulates system which is caught with feeling or emotional, that are middle-brain also big-brain. The purpose of gymnastics of brain is for knowing of describing knowlegment of teenager from 16 â 18 years old about gymnastics of brain.Â Â Â Â Â Â Â Â Â Â Â Research designwhich is used is deskriptif. The population is all of the teenager at SMK Putra Harapan, are 90 student. The sample is part of the teenager 16 â 18 years old are 20 respondens. Taken sample using quesioner then analized using taking data.Â Â Â Â Â Â Â Â Â Â Â The result show that knowlegment of teenager 16 â 18 years old about gymnastics brain is an enought knowledge are 14 respondens (70% ).Â Â Â Â Â Â Â Â Â Â Â The knowledge is one of factors that influences the describing knowlegement of teenager about of gymnastics brain. There is a knowledge that good important describing knowledgement of teenager about gymnastics brain will increase a good knowlegment. From theÂ result above, so is advised for teenager in order to increase knowlegment about gymnastics brain by healthy.Â Keywords : knowledge, teenager and gymnastics brain.